Contemporary issues in leadership (Boulder, Colo. Westview Press, 2012)
The seventh edition of this popular anthology continues its interdisciplinary approach to the topic of leadership and draws together new material describing the chief concerns facing leaders today. Reviewing hundreds of articles published since the sixth edition, William Rosenbach, Robert Taylor, and new coeditor Mark Youndt have collected the latest essays to clearly communicate the contradictions and paradoxes of leadership from historical to contemporary perspectives and global to individual considerations. The interdisciplinary approach to presentations of cutting-edge research and applications of leadership set this book apart from other collections. The seventh edition reemphasizes followership as an integral component of leadership, discusses the importance of leaders as mentors, helps navigate the hazards of leadership, and introduces a number of topics that will stimulate discussion. With classic selections retained and eighteen new essays added, the seventh edition of Contemporary Issues in Leadership presents a renewed framework for understanding leaders and leadership from a contemporary perspective.
Includes bibliographical references.
Keywords: Leadership